The lexical basis of grammatical borrowing : a Prince Edward Island French case study - King, Ruth Elizabeth, 1954- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2000)
This book is a detailed study of French-English linguistic borrowing in Prince Edward Island, Canada which argues for the centrality of lexical innovation to grammatical change. Chapters 1-4 present the theoretical and methodological perspectives adopted along with the sociolinguistic history of Acadian French. Chapter 5 outlines the basic features of Acadian French morphosyntax. Chapter 6 provides an overview of the linguistic consequences of language contact in Prince Edward Island. Chapters 7-9 consider three particular cases of grammatical borrowing: the borrowing of the English adverb bac.